Antibody to mycobacterial 65-kD heat shock protein in commercial antisera. - Hajeer, A H (1993)
Inhibition ELISA and immunoblotting were used to examine the antigenic cross-reactivity claimed to exist between mycobacterial 65-kD heat shock protein (hsp65) and human lactoferrin. Commercially available anti-lactoferrin antibodies produced using either Freund's complete (FCA) or Freund's incomplete adjuvant were tested for binding to recombinant mycobacterial hsp65. Both antibody preparations showed reactivity with hsp65, this being greater with the antibody produced using FCA. However, we found no evidence of a cross-reaction. Lactoferrin failed to inhibit anti-hsp65 reactivity, while hsp65 itself did. Affinity purified anti-lactoferrin antibody showed no reaction with hsp65 by ELISA or immunoblotting. These data suggest that commercial anti-lactoferrin preparations are contaminated with antibodies to hsp65. A commercial anti-albumin antibody also bound to hsp65 in ELISA, so this may be a more general phenomenon.